Antecedent‐Contained Deletion in Japanese: Support for the VP‐Ellipsis Analysis1. (22nd May 2018) - Abe, Jun
Abstract: In this article, I demonstrate that antecedent‐contained deletion (ACD) exists in Japanese, thereby supporting the V‐stranding VP‐ellipsis analysis, and that the infinite regress resolution with such ACD cases must be made by overt movement. I suggest that this way of infinite regress resolution is a universal property, demonstrating that English ACD cases can be analyzed along these lines. I also argue that what seems like a case of Japanese ACD involves argument ellipsis, even though it violates the anti‐c‐command requirement, and that the apparent violation is resolved by adopting the late insertion of adjuncts and the derivational definition of c‐command.